Reporting of harms in systematic reviews focused on naltrexone: a cross-sectional study - Schnitker, Joseph; Purcell, Lindsey; Garrett, Morgan; Flores, Holly; Wise, Audrey; Kee, Micah; Rucker, Brayden; Khan, Adam; Beaman, Jason; Vassar, Matt (Frontiers in Psychiatry, 2025)
BackgroundNaltrexone is a pharmacological intervention widely used for alcohol use disorder (AUD), opioid use disorder (OUD), and several off-label conditions. Systematic reviews (SRs) play a critical role in synthesizing data on the efficacy and safety of such interventions to inform clinical guidelines and decision-making. However, adequate reporting of harms in SRs remains inconsistent, limiting the ability to fully assess the safety profile of naltrexone. This study evaluates completeness of harms reporting and methodological quality in SRs focusing on naltrexone.MethodsA comprehensive search of MEDLINE, EMBASE, Epistemonikos, and the Cochrane Database of Systematic Reviews was conducted. The study employed masked, duplicate screening and data extraction. Included SRs were evaluated for completeness of harms reporting using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) harms checklist and other established frameworks. Methodological quality was appraised using the A MeaSurement Tool to Assess Systematic Reviews-2 (AMSTAR-2) tool, and primary study overlap among SRs was assessed through corrected covered area (CCA) analysis.ResultsA total of 87 SRs were included in the analysis. Only 1.1% (1/87) utilized severity scales to classify harms, and 4.6% (4/87) defined harms in their methods. Nearly half (48.3%) of SRs failed to address harms as either a primary or secondary outcome. A total of 82.8% (72/87) of SRs were rated as “critically low” quality by AMSTAR-2. Statistical analysis revealed a significant relationship between “critically low” AMSTAR-2 ratings and incomplete harms reporting (p = 0.0486). Additionally, four SR pairs demonstrated “high” overlap (>50%) of primary studies, accompanied by inconsistencies in harms reporting.ConclusionOur findings underscore the critical need for improved and standardized harms reporting in SRs on naltrexone. Inconsistent and incomplete reporting limits the ability of clinicians to fully assess the safety profile of naltrexone within systematic reviews. Adopting established frameworks such as PRISMA harms extensions and severity scales is imperative to enhance transparency and reliability in SRs. This study advocates for methodological improvements in SRs to support comprehensive safety evaluations and evidence-based prescribing of naltrexone.